1980
DOI: 10.1021/ja00542a003
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature carbon-13 magnetic resonance of solids. 1. Alkenes and cycloalkenes

Abstract: The 13C shift tensors for a large variety of olefins including some of the cyclic variety are reported at 20 K. On the basis of existing studies and symmetry arguments the orientation of the tensor elements can in general be assigned to specific molecular axes for the olefmic carbons. With this information conclusions are then drawn, relating trends in the various tensor elements to geometric and electronic effects. The method shows great promise in elucidation of the geometrical origins of chemical shifts. Of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
44
0

Year Published

1981
1981
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(57 citation statements)
references
References 0 publications
13
44
0
Order By: Relevance
“…Also, the theoretical average carbon shielding matches favorably with the experimental data in the same table. A fairly good qualitative agreement with Zilm et al [31], who reported the experimental carbon chemical shift tensor, has been found.…”
Section: Magnetic Properties and Current Densities In Ethylenesupporting
confidence: 88%
“…Also, the theoretical average carbon shielding matches favorably with the experimental data in the same table. A fairly good qualitative agreement with Zilm et al [31], who reported the experimental carbon chemical shift tensor, has been found.…”
Section: Magnetic Properties and Current Densities In Ethylenesupporting
confidence: 88%
“…ADF uses MOs that are generated from linear combinations of fragment orbitals (FOs) (108) to parameterize the electron density, according to Kohn and Sham (109), which is then used to calculate the total electronic energy. Using the calculated energy, the magnetic shielding is determined as described in Appendix B, and the total paramagnetic shielding contribution, s :: p , is arbitrarily decomposed into The contributions to paramagnetic shielding have been analysed according to pair-wise MO mixing several times before, although the analysis was often performed using approximate or empirical methods (110,111), qualitative discussions (40,(112)(113)(114)(115), or schematised representations of the MOs (116)(117)(118). More thorough treatments have tended to account for observed isotropic chemical shift values (39,119); however, relatively few (compared with the total number of accounts of observed/calculated CS) can be found where this discussion is extended to include anisotropic CS (38,41,43,48,120,121).…”
Section: Ramsey's Equations and Modern Computational Softwarementioning
confidence: 99%
“…techniques allow the determination of the chemical shift tensor components which provide a much richer source of information than the isotropic shielding values. Studies must be made in two directions, firstly on simple model compounds [33] and secondly, on families of compounds in which the geometry around the nucleus under study and the nature of the substituents are changed. The interpretation of the data which is directly related to the electronic structure and to the geometry remains a difficult problem.…”
Section: Ln[luence O[ the Geometrymentioning
confidence: 99%